Factors Abssociated With Occupational Irritant Contact Dermatitis In Cleaning Service - Raihan Fatihka Devi; Probo Yudha Pratama Putra; Dwi Nurwulan Pravitasari (Universitas Muhammadiyah Malang, 2023)
Occupational contact dermatitis is one of the occupational diseases which often arises due to contact with materials in the work environment. Cleaning service (CS) is an example of a job exposed to daily irritants that can cause skin irritation. The study used an analytic observational method with a cross-sectional approach. The population of CS throughout the University of Muhammadiyah Malang is 42 people with simple random sampling. The research data used a questionnaire from the Health and Safety Executive UK (HSE UK). The analytical technique used is the Fisher Exact and Kruskal Wallis test (alternative chi-square) in the bivariate test and logistic regression in the multivariate test. Bivariate analysis showed there was no specific relationship between the length of work (p= 0.178), duration of exposure (p= 0.068), and length of exposure (p= 1,000) in CS employees at the University of Muhammadiyah Malang, while in multivariate analysis it was not influenced by the same effect, significance (sig wald duration of exposure 0.851 and length of work 0.070). The incidence of occupational contact dermatitis caused by irritants often occurs after exposure, so there is no conclusion on the length of work, duration of exposure, and length of exposure.